The Implementation of REACT Strategy in Training Students’ Higher Order Thinking Skills (HOTS) - Elda Herlina; Ilmadi Ilmadi (Ta'dib, 2022)
This study aims to investigate the implementation of REACH strategies in training students' Higher Order Thinking Skills (HOTS) on critical thinking aspects. This research was a qualitative study. research type of research was descriptive research by using a qualitative approach. The research informants were student of the Mathematics Department of Mathematics and Science Faculty of Pamulang University.  Techniques used in data collection were observation, interview and documentation. The results of data analysis showed that REACT strategies can be used to improve HOTS skills in students’ critical thinking. Moreover it encouraged students to be active in participating in lectures. Students gave a very good response regarding the use of REACT strategies. This strategy must be used continuously for better learning outcomes, especially the Higher Order Thinking Skill, it can be exemplary achieved not only in critical thinking but also in the creative thinking.